Development of Proximity-Based COVID-19 Contact Tracing System Devices for Locally Virus Spread Prevention - Ainul Fitriyah Lubis; Basari Basari (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2022)
COVID-19 contact tracing is a preventive solution to slow the spread of the virus. Several countries have implemented manual contact tracing as well as digital tracking using smartphone applications. A proximity-based COVID-19 contact tracing system device using BLE (Bluetooth Low Energy) technology focuses on tracking and controlling the spread of the virus in local communities. The devices consist of a signal sending device (tag) and a signal receiving device (scanner). Suppose a system device is implemented in a factory. The tag will be used by employees by placing it in the front pocket of the factory employee's clothes or hooked on the shirt. The tag will continuously send a signal that will be read by the scanner. This received signal with the received signal strength indicator (RSSI) format will be used to calculate the distance between the scanner and the tag. Then the distance will be used to determine the coordinate point of the tag, with calculations using the trilateration algorithm. Therefore, the distance between tags can be obtained, while with signal fluctuation, the actual coordinate point cannot be obtained, yet proximity information can still be obtained by filtering distance data at a specified time interval that is less than the threshold value of the distance, 2 meters, then comparing the data with the overall data, resulting in a percentage value. A high percentage, above 80%, indicates the closeness between tags.